Neurocognitive function in clinically stable individuals with long-term bipolar I disorder: Comparisons with schizophrenia patients and controls - Pei-Yun Lin (Kaohsiung Journal of Medical Sciences, 2017)
This study compared the levels of the five domains of neurocognitive function—executive function, attention, memory, verbal comprehension, and perceptual organization—among clinically stable individuals with long-term bipolar I disorder, individuals with long-term schizophrenia, and a group of controls. We recruited a total of 93 clinically stable individuals with bipolar I disorder, 94 individuals with schizophrenia, and 106 controls in this study. Their neurocognitive function was measured using a series of neurocognitive function tests: the Wechsler Adult Intelligence Scale—Third Edition (WAIS-III), Line Cancellation Test, Visual Form Discrimination, Controlled Oral Word Association Test, Wisconsin Card Sorting Test, Continuous Performance Task, and Wechsler Memory Scale—Third Edition. Neurocognitive function was compared among the three groups through a multivariate analysis of variance. The results indicated that when the effect of age was controlled, clinically stable individuals with bipolar I disorder and those with schizophrenia demonstrated poor neurocognitive function on all tests except for the WAIS-III Similarity and Information and the Line Cancellation Test. The individuals with bipolar I disorder had similar levels of neurocognitive function compared with the schizophrenia group, but higher levels of neurocognitive function on the WAIS-III Comprehension, Controlled Oral Word Association Test, and Wechsler Memory Scale—Third Edition Auditory Immediate and Delayed Index and Visual Immediate and Delayed Index. The conclusions of this study suggest that compared with controls, individuals with long-term bipolar I disorder and those with long-term schizophrenia have poorer neurocognitive function, even when clinically stable. Individuals with long-term bipolar I disorder and those with long-term schizophrenia have similar levels of deficits in several domains of neurocognitive function.